Testing laboratory parameters of compost tea - Gorliczay, Edit; Pecsmán, Dénes; Tamás, János (Acta Agraria Debreceniensis, 2018)
During the industrial production of broiler chicken, a large amount of manure is produced, of which easily contained nitrogen content (without pre-treatment) is released into the atmosphere as an air pollutant. In our experiments, we aimed to prepare compost tea, also known as water extract of compost, from pre-treated poultry manure in order to create a product can be utilized as liquid nutrient supply. The poultry manure source was the Baromfi-Coop Ltd. located in Nyírjákó, Hungary, where it was treated by composting. As a result of this pre-treatment of the poultry manure, its nutrient parameters improve and nitrogen is present in a form that is better utilized for plants. Furthermore, this product is suitable for further utilization and also can be the base material for a brand-new product. For this reason the effects of compost/water ratio, incubation time, low oxygen level, and extraction time on the parameters of the resulted product were studied in the frame of developing new soil-life enhancing microbial product, so-called compost tea.Chemical parameters of the compost used as base material strongly determined the properties of the resulted compost tea, especially the ratio of the various nitrogen forms, their concentration and the salt content. It was found that adding water at a higher rate that means 1/40 and 1/50 mixing ratios results in more cost-effective production. In the experiment the compost tea were held under oxygen-poor conditions, therefore pH of the extractions decreased, which influenced the quality and quantity of their nutrient content.